Podium and/or Pulpit? D.F. Malan’s role in the politicisation of the Dutch Reformed Church, 1900-1959 (Historia, 2021)
EnglishThe Dutch Reformed Church has been regarded as an apartheid collaborator due to its close relationship with the National Party, earning it the label ìThe National Party at prayerî. This perception is strengthened by the fact that a number of prominent Afrikaner Nationalist politicians were former clergymen. One of the most prominent, was D.F. Malan, the first of the apartheid prime ministers and the only former Dutch Reformed minister to occupy the position of head of government. The assumption is easily made that Malan exchanged the pulpit for the podium in order to preach to the entire volk, thus drawing party and church closer together. This article examines Malanís views on church and state, as well as his relationship with the church after his entry into politics in 1915. It finds that he supported the separation of the institutions of church and state, but believed that both institutions were accountable to God and hence, had to adhere to the same belief-system: God-given Afrikaner Nationalism. Malan never explained this distinction in his thinking to his followers. In his political dealings, he refrained from interfering in church affairs, but vaguely referred to cooperation between the institutions, although that never took any concrete form.    AfrikaansDie Nederduitse Gereformeerde (NG) Kerk dra die beeld van apartheid meeloper danksy diÈ kerk se noue bande met die Nasionale Party, soveel so dat daar spottenderwys na die kerk as ìDie Nasionale Party in gebedî verwys is. Dit word versterk deur die feit dat ŉ aantal prominente Afrikanerpolitici eertydse predikante was, met D.F. Malan as die voorbok: die enigste voormalige NG predikant wat regeringshoof geword het. Die aanname word maklik gemaak dat Malan die preekstoel vir die podium verruil het sodat hy vir die hele volk kon preek ñ en sodoende die kerk en die party bymekaar gebring het. Hierdie artikel ondersoek Malan se denke ten opsigte van kerk en staat, sowel as sy verhouding met die kerk n· sy toetrede tot die politiek in 1915. Die bevinding is dat hy die skeiding tussen die instellings van kerk en staat ondersteun het, maar terselfdertyd geglo het dat kerk en staat tot dieselfde geloofstelsel verbind moet wees, naamlik God-gegewe Afrikanernasionalisme. Malan het nooit hierdie fyn onderskeid aan sy volgelinge verduidelik nie. Wat sy politieke optrede aanbetref, het Malan nooit by kerksake ingemeng nie, maar wel vaagweg voorgestel dat die twee instellings moet saamwerk, hoewel die voorstel nooit enige tasbare vorm aangeneem het nie.
Keywords: 1914 Rebellion; 1948 election; Afrikaner Nationalism; Afrikaners; apartheid; church; D.F. Malan; Die Burger; Dutch Reformed Church; Romanticism; Sauer Report; South Africa; state; Stellenbosch; theology; 1914 Rebellie; 1948 verkiesing; Afrikanernasionalisme; geskiedenis; godsdiens; kerk; Nasionale Party; Nasionalisme; Nederduitse Gereformeerde Kerk; NeoCalvinisme; Romantisisme; Sauerverslag; staat; Suid-Afrika; teologie